EVALUASI PROGRAM PELATIHAN: STUDI KASUS BAGIAN MESIN LOGAM DI BLK SLEMAN TAHUN 2017 - Slamet Priyanto; Rabiman Rabiman (Jurnal Taman Vokasi, 2017)
This research aims to get an overview of: metal machine training curriculum; metal machine trainee qualification; the qualifications of trainers (educator) metal machine; metal machine skills practice facilities; the process of metal machine skills training; and competences achieved by the trainee machine metal. The methods used to collect data in this study are: (1) an interview with head of BLK metal machines and instructors to get the data of the curriculum, metal machine practice worksheets, learning methods, evaluation tools; (2) the observation data to get the process of education and training; (3) documentation to get the data infrastructure workshop machinery metal. To keep the validity of qualitative data in this study, performed the triangulation techniques. Input in training consists of instructors; participants of the training; training materials; training tools in the form of the machine with his supporters, machinery and equipment, the infrastructure of the training and Training curriculum-oriented metal machine KKNI. The process of metal machine includes two training activities. Proponents of the theory of practice activities carried out in the room of the theory and practice of the activities carried out in the workshop. Evaluation of products in the study found that the competence achieved are: 50% of the participants achieved 8 competencies; 25% of the participants achieved the 7 competencies; 18.75% of participants achieving 6 competencies; and 6.25% of the participants achieved competency 5 of 8 competencies to be achieved by the participants of the training at the end of training.